An efficient inelastic approach using SCM/RPHM coupling to study reinforced concrete beams, columns and frames under fire conditions. (15th September 2020) - Pires, Dalilah; Barros, Rafael C.; Silveira, Ricardo A.M.; Lemes, Ígor J.M.; Rocha, Paulo A.S.
Highlights: A computational system for thermo-structural analysis is developed. A concentrated plasticity approach for thermo-structural analysis is proposed. Strain Compatibility Method is used for full yield curves construction. The cross-section temperature field are calculated for any faces under fire. The displacements and internal forces are obtained with the temperature increase. Abstract: This work has as its main objective the study of the behavior of reinforced concrete beams, columns and structural frames in a fire situation. To do so an efficient numerical formulation was developed, implemented and evaluated. When exposed to high temperatures, the characteristics of the materials deteriorate, resulting in a considerable loss of strength and stiffness of the structure. The CS-ASA (Computational System for Advanced Structural Analysis) was used to achieve the objective. This computer system was expanded for advanced analysis of structures in fire conditions, taking advantage of the existing features and adding new ones. Two new computational modules were created: CS-ASA/FA (Fire Analysis) and CS-ASA/FSA (Structural Fire Analysis). The first one was used to determine the temperature field in the structural elements' cross-section through thermal analysis by the Finite Element Method (FEM) in permanent and transient regimes. The second was created to perform the second-order inelastic analysis of structures under fire using the FEM formulations based on the Refined Plastic Hinge Method (RPHM) and the Strain Compatibility Method (SCM) coupling, which can be considered a unique feature of the present study. The use of SCM allows for a more realistic analysis against the design codes prescriptions. Consequently, even under high temperatures, SCM is used for evaluation of both bearing capacity and stiffness parameters. The results of the nonlinear analysis in a fire situation for eight structural elements and systems with different geometries, boundary, heating and loading conditions are in good agreement with the numerical and experimental results found in the literature.